(untitled) (Journal of the Sociology and Theory of Religion, 2025)
The comparative analysis that we aspire to carry out, is considered a crossroads of two different cultures, reproduced, in the inter-analytical context, by the Islamic Sacred Text and the Ibero-American literary text; in particular, Uruguayan. We try, following the elucovery in question, to shed light on the phenomenology of interaction and reflection of the human being according to an instinctive and conventional logic, conditioned by the sensitivity and limitation of its psychological and biological constitution; while its Creator governs its vital adventures based on emblematic stations that determine its existential itinerary, in a framework surrounded, in advance, by Determinism. In the orbit of the Sacred Text, the three capital events that portray the verses (65 to 82) of the "Surah of Al-Kahf" attest to the total incongruity between the dimension of human logic, represented by the bewilderment of Moses, and the indimension of divine logic whose causality is deciphered by Lord Al-Khadir; testimony that is confirmed, in the area of the literary text, by the failure of human logic embodied by the protagonist of "The truce": Martín Santomé, before the predetermination of divine logic, transliterated by Mario Benedetti.